Pelatihan Master of Ceremony Dalam Bahasa Inggris bagi Para Santri Taman Pendidikan Al-Qur’an (TPQ) Nurul Yaqin Bandar Lampung - Siswoyo Siswoyo; Fatma Yuniarti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Good preparation is essential for English event hosts to perform effectively. At a minimum, they should be able to read texts in English with confidence. Taman Pendidikan Al-Qur’an (TPA)